Case report: Novel frameshift mutation in LAMA2 gene causing congenital muscular dystrophy type 1A - Diaz-Lombana, Natalia; Diaz-Ordoñez, Lorena; Gutierrez-Medina, Juan David; Pachajoa, Harry (Frontiers in Genetics, 2023)
Congenital muscular dystrophy type 1A (CMD1A) is a rare autosomal recessive disorder caused by mutations in the LAMA2 gene. CMD1A is characterized by peripheral hypotonia and muscle weakness from the first months of life, cerebral white matter abnormalities, and elevated creatine phosphokinase (CPK) levels. We describe an 8-year-old girl from Colombia with clinical features compatible with CMD1A, severe scoliosis corrected with surgery, and feeding difficulty corrected with a gastrostomy. Whole-exome sequencing identified two heterozygous variants: a reported nonsense variant (LAMA2 NM_000426.3:c.4198C>T) and a novel likely pathogenic variant (LAMA2 NM_000426.3:c.9227_9243dup). This is the first genetically confirmed case of CMD1A in Colombia and the first report of the c.9227_9243dup variant causing CMD1A.